2015
DOI: 10.1021/jf5042307
|View full text |Cite
|
Sign up to set email alerts
|

Demethoxycurcumin Modulates Human P-Glycoprotein Function via Uncompetitive Inhibition of ATPase Hydrolysis Activity

Abstract: Curcuminoids are major components of Curcuma longa L., which is widely used as spice in food. This study aimed at identifying whether curcumin, demethoxycurcumin, and bisdemethoxycurcumin could modulate efflux function of human P-glycoprotein and be used as chemosensitizers in cancer treatments. Without altering P-glycoprotein expression levels and conformation, the purified curcuminoids significantly inhibited P-glycoprotein efflux function. In rhodamine 123 efflux and calcein-AM accumulation assays, demethox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…This strategy could be used to reverse multidrug resistance against select cancers. In a study by Teng, Hsieh, Hung, and Lin (2015) it was shown that DMC inhibited P-gp (Table 1)…”
Section: Dmc As a Chemosensitizing Agentmentioning
confidence: 99%
“…This strategy could be used to reverse multidrug resistance against select cancers. In a study by Teng, Hsieh, Hung, and Lin (2015) it was shown that DMC inhibited P-gp (Table 1)…”
Section: Dmc As a Chemosensitizing Agentmentioning
confidence: 99%
“…The method has been described in our previous research [9]. The calcein fluorescence generated within the cells was detected by BioTek Synergy HT Multi-Mode Microplate Reader using excitation wavelength 485 nm and emission wavelength 528 nm at 37 • C temperature every 3 min for 30 min.…”
Section: Intracellular Calcein Accumulation Assaymentioning
confidence: 99%
“…The method has been described in our previous research [9]. The relative ABCB1 mRNA expression levels were normalized to the amount of GAPDH in the same cDNA and evaluated by StepOnePlus TM Real-Time PCR System (Applied Biosystems ® , Waltham, MA, USA).…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%
See 2 more Smart Citations